The Relationship Between Spiritual Intelligence Level and Santri Obedience in Implementing Regulation - Muhammad Shalahuddin; Waslah Waslah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The objectives of this research are; 1) to describe the spiritual intelligence of the students of the Sunan Ampel Islamic Boarding School Jombang. 2) to describe the students' compliance in carrying out the regulations of the Sunan Ampel Islamic Boarding School Jombang. 3) to analyze whether or not there is a relationship between the level of spiritual intelligence and the obedience of students in implementing the regulations of the Sunan Ampel Islamic Boarding School Jombang. The method used in this research is quantitative research. The population in this study were all students of Sunan Ampel Jombang, according to the caregivers, which amounted to 150 students, while the sample in this study was 101 students. Data collection techniques used in this study are observation, interviews, questionnaires and documentation. The data analysis used in this research is product moment correlation analysis. Based on the results of the study showed that the Spiritual Intelligence of the Sunan Ampel Islamic boarding school students obtained 41.9 results. Based on this number, it can be concluded that the average score of the Spiritual Intelligence of the Santri is between 40-50 with very high criteria, while the obedience of the students in carrying out the rules is 41.0. Based on this number, it can be concluded that the average student awareness in carrying out the rules is between 30-40 with high criteria. Based on the calculation of the product moment correlation that has been done, it can be seen that rxy or rcount with a total of 0.640 is greater than rtable, so Ha is accepted, that is, there is a relationship between the level of spiritual intelligence and the obedience of students in carrying out the regulations of the Sunan Ampel Islamic Boarding School Jombang.